TEORI MUBADALAH DAN APLIKASINYA DALAM PENELITIAN GENDER - Syarifudin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
Gender discourse in Islam has continued to evolve alongside growing critical awareness of patriarchal bias embedded in classical exegetical and juridical traditions. Various strands of Islamic feminism have sought to reconstruct more gender-just interpretations of religious texts; however, these approaches often encounter normative resistance within mainstream Muslim communities. This article aims to examine the theory of Mubadalah, developed by Faqihuddin Abdul Kodir, as an alternative hermeneutical framework in Islamic gender studies. Employing a qualitative library-based research method, this study utilizes conceptual and hermeneutical analysis, combined with critical engagement with global Islamic feminist scholarship. The findings reveal that Mubadalah offers a relational interpretive paradigm grounded in the principle of reciprocity, positioning men and women as equal moral subjects in receiving religious commands, prohibitions, and ethical teachings. Unlike certain strands of global Islamic feminism that emphasize structural critiques of classical interpretive authority, Mubadalah operates from within the Islamic textual and scholarly tradition by foregrounding maq??id al-shar?‘ah as its primary ethical orientation. This approach not only reconstructs gender-biased interpretations of religious texts but also generates significant theoretical and practical implications for public policy, family relations, and Islamic education. This article contributes to Islamic gender studies by positioning Mubadalah as an indigenous Islamic gender hermeneutics that mediates the tension between global Islamic feminism and normative Islamic tradition. The study demonstrates that Mubadalah holds transformative and sustainable potential for advancing gender justice within contemporary Muslim societies.